Mendengarkan Murattal Al-Qur'an untuk Menurunkan Tingkat Insomnia - Etik Dwi Wulandari; Nita Trimulyaningsih (Universitas Islam Indonesia, 2015)
This research aimed to understand the effect of listening murattal Al-Qur'an to insomnia score. The hypothesis of this research is listening murattal Al-Qur'an can reduce insomnia level. Subjects participated in this research were two university students from Faculty of Psychology and Social Culture, major Psychology, Department of Psychology at the Islamic University of Indonesia, who were diagnosed with insomnia. The data was collected with KSPBJ - Insomnia Rating Scale, monitoring scale and interview. Data analysis showed that there was effect of listening murattal Al-Qur’an to reduce insomnia level, thus the research hypothesis was accepted.Keywords: Listening Murattal Al-Qur'an, level of Insomnia